(untitled) - Gilmore, Gordon (Chichester, England, 2008)
This book provides comprehensive coverage of the whole gamma-ray detection and spectrum analysis processes. Drawn on many years of teaching experience to produce this uniquely practical volume, issues discussed include the origin of gamma-rays and the issue of quality assurance in gamma-ray spectrometry. This new edition also covers the analysis of decommissioned nuclear plants, computer modelling systems for calibration, uncertainty measurements in QA, and many more topics
Keywords: Gamma ray spectrometry,Phổ tia Gama